Tipos de abonos orgánicos y fertilizante foliar en las características agronómicas y rendimiento de Solanum lycopersicum L. variedad Rio Grande, Loreto - Ortiz Silva, Smith Esmeralda (2025)
The present experiment was conducted in a horticultural field located in UTM 9756236 North and 681245 South, of the district of Iquitos, in a clay loam soil with low fertility. The Rio Grande tomato variety was studied, evaluating the effect of two types of organic fertilizers: Poultry Manure (Factor A: a1) and Compost from organic waste (Factor A: a2), in combination with the application of a foliar fertilizer (Factor B: b1: Without foliar fertilizer and b2: With foliar fertilizer. The treatments evaluated were: T1: Poultry manure without foliar fertilizer; T2: Manure with foliar fertilizer; T3: Compost without foliar fertilizer and T4: Compost with foliar fertilizer. The effects of the research indicated that the T2 treatment (poultry manure with foliar fertilizer) obtained the most favorable results, highlighting the weight in grams of fruits per plant (1,682.44 g) which suggests a positive interaction between poultry manure and foliar fertilizer, pointing out that the combination of poultry manure and foliar fertilizer constitutes an effective strategy to maximize the weight of Rio Grande tomato fruits in soils of low fertility.